1998
DOI: 10.1136/jcp.51.7.502
|View full text |Cite
|
Sign up to set email alerts
|

The identification of salicylates as normal constituents of serum: a link between diet and health?

Abstract: Aim-To examine sera for the presence of salicylic acid and 2,3-and 2,5-dihydroxybenzoic acids (2,3-and 2,5-DHBA), in individuals not taking salicylate drugs. Methods-Extracts of acidified serum samples were analysed by high performance liquid chromatography with electrochemical detection. The chromatographic conditions were altered, and the retention times of the unknown compounds compared against authentic salicylic acid, 2,3-DHBA, and 2,5-DHBA. Serum samples (some spiked with salicylic acid) were incubated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 19 publications
1
42
0
1
Order By: Relevance
“…Although there is some uncertainty concerning the quantitative estimation of the salicylate content of plant-based foods, evidence for dietary as opposed to pharmaceutical sources is suggested by the detection of salicylic acid and associated metabolites in plasma and urine of individuals not taking aspirin or related preparations (Paterson et al 1998;Blacklock et al 2001;Baxter et al 2002). Moreover, serum ( Red wine 3 .…”
Section: Evidence For Dietary Uptake Of Salicylic Acidmentioning
confidence: 99%
“…Although there is some uncertainty concerning the quantitative estimation of the salicylate content of plant-based foods, evidence for dietary as opposed to pharmaceutical sources is suggested by the detection of salicylic acid and associated metabolites in plasma and urine of individuals not taking aspirin or related preparations (Paterson et al 1998;Blacklock et al 2001;Baxter et al 2002). Moreover, serum ( Red wine 3 .…”
Section: Evidence For Dietary Uptake Of Salicylic Acidmentioning
confidence: 99%
“…After administration, aspirin undergoes rapid hydrolysis to generate salicylic acid (SA), and it is this phenolic acid that may be responsible for the persistence of the anti-in£ammatory e¡ect of aspirin. 2 Paterson et al, 3 using high-performance liquid chromatography (HPLC), gas chromatography^mass spectrometry (GCMS) and salicylate hydroxylase, demonstrated that SA and two of its hydroxylated metabolites were present in the serum of people who had not taken salicylate drugs, and they suggested that these phenolic acids may have had a dietary origin. Swain et al 4 determined SA in foodstu¡s using HPLC with UV detection and estimated that the dietary intake of SA was in the range 70^1100 mol per person per 24 h. Janssen et al 5 examined acid-treated urine using HPLC with £uorescence detection, and suggested that the dietary intake of SA was about 10 mol per person per 24 h. However, neither Swain et al nor Janssen et al had characterized the compound(s) they had determined.…”
Section: Introductionmentioning
confidence: 99%
“…Salicylates may be found as constituents of a normal diet (fruit and vegetables) and, notwithstanding our ignorance of the molecular pathways they activate in the gut epithelium, one can reasonably infer that ingestion of such dietary salicylates may contribute to the health of an individual by reducing colorectal cancer incidence (39,44). In an effort to understand the molecular basis of the growth inhibitory effect of ASA against cancer cells we examined a number of derivatives of salicylic acid.…”
Section: Discussionmentioning
confidence: 99%